Associations of patient characteristics, disease stage, and biopsy technique with the diagnostic quality of core needle renal biopsy specimens from dogs with suspected kidney disease - Crivellenti, Leandro Z. [UNESP]; Cianciolo, Rachel; Wittum, Thomas; Lees, George E.; Adin, Christopher A. (American Veterinary Medical Association (AVMA), 2018)
OBJECTIVE To identify factors affecting the diagnostic quality of core needle renal biopsy specimens from dogs with suspected kidney disease. DESIGN Cross-sectional study. ANIMALS 522 client-owned dogs with suspected kidney disease for which core needle renal biopsy specimens (n = 1,089) were submitted to the International Veterinary Renal Pathology Service for evaluation and inclusion in their database. PROCEDURES Data regarding dog signalment, clinical variables, biopsy method, needle brand and gauge, biopsy results, and other variables were extracted from the database. Variables were tested for association with 3 outcomes of light microscopic evaluation of core specimens: number of glomeruli per core specimen, obtainment of < 10 glomeruli, and presence or absence of renal medullary tissue. RESULTS Number of glomeruli per core specimen was significantly associated with needle gauge, dog age, serum creatinine concentration, and degree of proteinuria, whereas biopsy method and submitting hospital were significantly associated with the presence of renal medullary tissue in specimens. Mean numbers of glomeruli per core specimen obtained with 14-or 16-gauge needles were similar, but both were significantly greater than the mean number obtained with 18-gauge needles. Needle gauge had a similar association with the likelihood of obtaining < 10 glomeruli in a core specimen. Specimens obtained via laparotomy or laparoscopic approaches more commonly contained medullary tissue than those obtained by ultrasound-guided approaches. CONCLUSIONS AND CLINICAL RELEVANCE Overall, findings suggested that ultrasound-guided biopsy with a 16-gauge needle should maximize the diagnostic quality of renal biopsy specimens from dogs with suspected kidney disease, while avoiding potential adverse effects caused by larger needles.